2006
DOI: 10.1016/j.ijsolstr.2005.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear behaviour of piezoceramics under weak electric fields

Abstract: Piezoceramic materials exhibit different types of nonlinearities under different combinations of electric and mechanical fields. When excited near resonance in the presence of weak electric fields, they exhibit typical nonlinearities similar to a Duffing oscillator such as jump phenomena and presence of superharmonics in the response spectra. In order to model such nonlinearities, a nonlinear electric enthalpy density function (using quadratic and cubic terms) valid for a general 3-D piezoelectric continuum ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…For repeated indices, Einstein's summation convention is implied in the tensorial expressions. In order to model the nonlinearities in a coupled piezoelectric medium, the linear electric enthalpy density function was modified by Samal et al (2006a) incorporating higher order terms (viz., quadratic and cubic in strain and electric field vector) in the energy expression of the coupled piezoelectric domain and hence is written as…”
Section: Generalized Nonlinear Constitutive Equation Of the Piezoelecmentioning
confidence: 99%
See 3 more Smart Citations
“…For repeated indices, Einstein's summation convention is implied in the tensorial expressions. In order to model the nonlinearities in a coupled piezoelectric medium, the linear electric enthalpy density function was modified by Samal et al (2006a) incorporating higher order terms (viz., quadratic and cubic in strain and electric field vector) in the energy expression of the coupled piezoelectric domain and hence is written as…”
Section: Generalized Nonlinear Constitutive Equation Of the Piezoelecmentioning
confidence: 99%
“…From the experiments carried out at different electric field magnitudes, it was observed that the damping properties of the material depends upon the magnitude of electric field excitation and the dependence is not linear (as opposed to the linear viscous damping assumption in many analyses) especially for soft PZTs. In order to better describe the damping in the coupled piezoelectric domain, a generalized nonlinear damping model was developed by Samal et al (2006a), which considers linear as well as higher order time derivatives of both strain and electric field vector in the virtual work expression by damping forces dW D and the expression for dW D , is written as (Samal et al, 2006a)…”
Section: Hamilton's Principlementioning
confidence: 99%
See 2 more Smart Citations
“…The authors are conscious that the stated problem has been approached successfully using FEM (finite element method) schemes [12][13][14][15]; however, the ease of model construction and availability of direct time domain calculations when using FDTD models justifies their introduction for many particular case studies. In fact, in echoimpulse techniques and directional radiation problems, the time domain knowledge of physical variables is a priority, and it is difficult to obtain them from the inverse-Fourier transform of numerically-obtained eigenvalues.…”
mentioning
confidence: 99%